Pathophysiological and clinical findings of Covid-19 virus infection in respiratory system: A anatomist’s view point - Yashiro, Takashi; Stujanna, Endin Nokik; Indriyati, Leli Hesti; Sukarya, Wawang Setiawan (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2020)
No abstract